Withdrawal symptoms in abstinent methamphetamine-dependent subjects - Zorick, Todd; Nestor, Liam; Miotto, Karen; Sugar, Catherine; Hellemann, Gerhard; Scanlon, Graham; Rawson, Richard; London, Edythe D. (Addiction (Abingdon, England), 2010)
ABSTRACT Aims  Withdrawal symptoms have been linked to a propensity for relapse to drug abuse. Inasmuch as this association applies to methamphetamine (MA) abuse, an understanding of the course of MA withdrawal symptoms may help to direct treatment for MA dependence. Previous studies of symptoms manifested during abstinence from MA have been limited in size and scope. We asked (i) whether debilitating psychological and/or physical symptoms appear during the first several weeks of MA abstinence, (ii) how craving for MA evolves and (iii) whether psychiatric symptoms (e.g. depression, psychosis) persist beyond a month of abstinence. Design  A study of MA‐dependent participants, who initiated and maintained abstinence from the drug for up to 5 weeks, compared to a matched healthy comparison group. Setting  In‐patient research hospital ward (MA‐dependent subjects) and out‐patient (comparison subjects). Participants  Fifty‐six MA‐dependent and eighty‐nine comparison subjects. Measurements  Rater‐assessed MA withdrawal questionnaire and self‐report assessment of craving (MA‐dependent subjects) and self‐report assessment of psychiatric symptoms (both groups). Findings  At study entry, MA‐dependent subjects exhibited a wide range in severity of depressive symptoms, with the average score at a mild–moderate level of severity. Symptoms of psychosis were also prevalent. While depressive and psychotic symptoms largely resolved within a week of abstinence, craving did not decrease significantly from the time of initiating abstinence until the second week, and then continued at a reduced level to the fifth week. Conclusions  Depressive and psychotic symptoms accompany acute withdrawal from methamphetamine but resolve within 1 week. Craving is also present and lasts at least 5 weeks.